2020
DOI: 10.7554/elife.50962
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms that allow cortical preparatory activity without inappropriate movement

Abstract: We reveal a novel mechanism that explains how preparatory activity can evolve in motor-related cortical areas without prematurely inducing movement. The smooth eye movement region of the frontal eye fields (FEFSEM) is a critical node in the neural circuit controlling smooth pursuit eye movement. Preparatory activity evolves in the monkey FEFSEM during fixation in parallel with an objective measure of visual-motor gain. We propose that the use of FEFSEM output as a gain signal rather than a movement command all… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 62 publications
1
9
0
Order By: Relevance
“…Although we consider SC activity during the delay period to be preparatory in the sense that it is related to the enhancement or hindrance of rapid saccade initiation following the go cue, it does not have "motor potential." In the smooth pursuit system of the FEF, neural activity was found to have motor potential, with partially overlapping subpopulations contributing to both the preparation and execution of movement (Darlington and Lisberger, 2020). However, this does not seem to be the case for the SC, at least in the context of saccades.…”
Section: Does Sc Delay Activity Resemble a Preparatory Signal?mentioning
confidence: 95%
“…Although we consider SC activity during the delay period to be preparatory in the sense that it is related to the enhancement or hindrance of rapid saccade initiation following the go cue, it does not have "motor potential." In the smooth pursuit system of the FEF, neural activity was found to have motor potential, with partially overlapping subpopulations contributing to both the preparation and execution of movement (Darlington and Lisberger, 2020). However, this does not seem to be the case for the SC, at least in the context of saccades.…”
Section: Does Sc Delay Activity Resemble a Preparatory Signal?mentioning
confidence: 95%
“…The activity of the primary motor cortex (M1) during movement preparation and execution plays a key role in the control of voluntary limb movement [1,2,3,4,5,6,7]. Classic studies of motor preparation were performed in a delayed-reaching task setting, showing that firing rates correlate with task-relevant parameters during the delay period, despite no movement occurring [8,9,10,11,12,13,14,14,15,16,17]. More recent works have shown that preparatory activity is also displayed before non-delayed movements [18], that it is involved in reach correction [19], and that when multiple reaches are executed rapidly and continuously, each upcoming reach is prepared by the motor cortical activity while the current reach is in action [20].…”
Section: Introductionmentioning
confidence: 99%
“…The activity of the primary motor cortex (M1) during movement preparation and execution plays a key role in the control of voluntary limb movement ( Evarts, 1968 ; Whishaw et al, 1993 ; Whishaw, 2000 ; Graziano et al, 2002 ; Harrison et al, 2012 ; Scott, 2012 ; Brown and Teskey, 2014 ). Classic studies of motor preparation were performed in a delayed-reaching task setting, showing that firing rates correlate with task-relevant parameters during the delay period, despite no movement occurring ( Hanes and Schall, 1996 ; Tanji and Evarts, 1976 ; Churchland et al, 2006a ; Churchland et al, 2006b ; Messier and Kalaska, 2000 ; Dorris et al, 1997 ; Glimcher and Sparks, 1992 ; Glimcher and Sparks, 1992 ; Wurtz and Goldberg, 1972 ; Darlington et al, 2018 ; Darlington and Lisberger, 2020 ). More recent works have shown that preparatory activity is also displayed before non-delayed movements ( Lara et al, 2018 ), that it is involved in reach correction ( Ames et al, 2019 ), and that when multiple reaches are executed rapidly and continuously, each upcoming reach is prepared by the motor cortical activity while the current reach is in action ( Zimnik and Churchland, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the pursuit system, motor preparation modulates the state of visual-motor gain (Kodaka & Kawano, 2003;Tabata et al, 2006). Preparatory enhancement of visual-motor gain has been linked to FEFSEM neurons, which display preparatory ramps of firing during fixation that leads up to pursuit (Darlington & Lisberger, 2020;Mahaffy & Krauzlis, 2011;Tanaka & Fukushima, 1998). Expectation of faster target motion causes larger amplitudes of preparatory activity and larger behavioral readouts of visual-motor gain (Darlington et al, 2018;Darlington et al, 2017).…”
Section: Motor Preparation In the Pursuit System Affects Visual Motio...mentioning
confidence: 99%
“…Visual-motor gain and FEFSEM have been implicated in many higher-order features of pursuit, for example reward (Raghavan & Joshua, 2017), motor learning (Li & Lisberger, 2011), and modulation of behavior by experience-dependent expectation of target motion (Darlington et al, 2018). Importantly, both visual-motor gain and preparatory activity in FEFSEM are dialed up in preparation for smooth pursuit eye movements (Darlington & Lisberger, 2020;Tabata et al, 2006). It is possible to probe visual-motor gain by measuring the eye movement responses to brief pulses of target motion.…”
Section: Introductionmentioning
confidence: 99%